Quality of life and coping strategies of outpatients with a depressive disorder in maintenance therapy – a cross-sectional study - Holubova M (Dove Medical Press, 2017)
Michaela Holubova,1,2 Jan Prasko,1 Marie Ociskova,1 Ales Grambal,1 Milos Slepecky,3 Marketa Marackova,1 Dana Kamaradova,1 Marta Zatkova3 1Department of Psychiatry, Faculty of Medicine and Dentistry, Palacky University Olomouc, University Hospital Olomouc, Olomouc, 2Department of Psychiatry, Hospital Liberec, Liberec, Czech Republic; 3Department of Psychology Sciences, Faculty of Social Science and Health Care, Constantine the Philosopher University in Nitra, Nitra-Chrenova, Slovak Republic Background: The quality of life (QoL) is a multidimensional view that represents all aspects of patient well-being in various areas of patient life. Specific coping strategies may be connected to both the QoL and the severity of mental disorder. The aim of this investigation was to examine the relationship between the QoL and the coping strategies of outpatients with a depressive disorder.Methods: Eighty-two outpatients, who met the criteria of the International Classification of Diseases, Tenth Revision, for a depressive disorder, were enrolled in the cross-sectional study. Data on sociodemographic and clinical variables were obtained from the medical records. Individuals filled the following standardized questionnaires: Quality of Life Satisfaction and Enjoyment Questionnaire, Stress Coping Style Questionnaire, and Clinical Global Impression. Multiple regression analyses with backward elimination were performed to discover the most influential factors contributing to QoL.Results: The participants with a depressive disorder showed an overuse of negative coping strategies, especially escape tendency and resignation. A positive self-instruction strategy was used by the patients less often. The coping strategies were significantly associated with the QoL. A more frequent use of positive coping strategies had a positive association with the QoL. The main factors related to QoL were the subjective severity of the disorder, employment, and positive coping strategies.Conclusion: The study confirmed the relationship between QoL and the coping strategies of outpatients with a depressive disorder. Keywords: coping strategies, quality of life, depressive disorder